2023
DOI: 10.3390/pharmaceutics15010259
|View full text |Cite
|
Sign up to set email alerts
|

ZnO@ZIF-8 Nanoparticles as Nanocarrier of Ciprofloxacin for Antimicrobial Activity

Abstract: Numerous antimicrobial drugs have been prescribed to kill or inhibit the growth of microbes such as bacteria, fungi, and viruses. Despite the known therapeutic efficacy of these drugs, inefficient delivery could result in an inadequate therapeutic index and several side effects. In order to overcome this adversity, the present study investigated antibiotic drug loading in zeolitic imidazolate frameworks (ZIFs), in association with ZnO nanoparticles with known antimicrobial properties. In an economic synthesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…Here, we used ZIF-8 NPs instead of other biomaterials including mesoporous bioglass as vehicles of Ce ions, although mesoporous bioglass has many advantages . Aided by the generation of ROS and the accumulation of increased electrostatic attraction on the bacterial cell membrane, Zn 2+ is a potent antibacterial agent effective against both Gram-negative and Gram-positive bacteria. , ZIF-8 NPs are antibacterial when Zn 2+ is released sustainedly from nano ZIF-8. In this study, 2%, 4%, and 8% Ce@ZIF-8 all demonstrated a sustained release of Zn and Ce ions in complete DMEM (Figure E,F).…”
Section: Resultsmentioning
confidence: 99%
“…Here, we used ZIF-8 NPs instead of other biomaterials including mesoporous bioglass as vehicles of Ce ions, although mesoporous bioglass has many advantages . Aided by the generation of ROS and the accumulation of increased electrostatic attraction on the bacterial cell membrane, Zn 2+ is a potent antibacterial agent effective against both Gram-negative and Gram-positive bacteria. , ZIF-8 NPs are antibacterial when Zn 2+ is released sustainedly from nano ZIF-8. In this study, 2%, 4%, and 8% Ce@ZIF-8 all demonstrated a sustained release of Zn and Ce ions in complete DMEM (Figure E,F).…”
Section: Resultsmentioning
confidence: 99%
“…The alteration in the chemical composition, thermal behavior, and crystalline structure of these modified PU surfaces was evaluated using water contact angle measurement, FTIR, DSC, and XRD, respectively. Ciprofloxacin (a second-generation fluoroquinolone) , was used as a model drug for this study. The drug was incorporated onto the surface by using the dip-coating technique.…”
Section: Introductionmentioning
confidence: 99%
“…Staphylococcus aureus were cultivated on blood agar and exposed to pure CO 2 , a standard anaerobic gas, or air, over a period of 24 h [ 4 ]. Recent studies on methicillin-resistant S. aureus (MRSA) were concerned with antibacterial material and pathogeny [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. The survival of Escherichia coli , P. aeruginosa , Enterobacter cloacae , and Klebsiella pneumonia were investigated in bottled still water and demonstrated a reduction of colony-forming units (CFUs) over a period of twenty days [ 13 ].…”
Section: Introductionmentioning
confidence: 99%